Policymaking in Ontario for Older Adults' Self-Management of Disease and Disability Using Information and Communication Technologies - Gauthier-Beaupré, Amélie (Université d'Ottawa / University of Ottawa, 2023)
Policymaking on health issues has evolved since the early 2000s. Since then, there have been significant changes in society including increased aging of the population and the emergence of technology. However, the evolution of policymaking and current approaches to policymaking cross-cutting in those areas are not well documented. The purpose of this dissertation is to explore the factors that influence the development and implementation of a framework for policymaking specific to the topic of older adults’ self-management of disease and disabilities using information and communication technologies (ICT). I conducted one large study with three phases, using Ontario as a case study, to document the history and portray current approaches to policymaking in this area, and finally, to develop and validate a conceptual framework for policymaking. Grounded in Walt and Gilson’s model for policy analysis, we performed the following: Phase 1, which is presented in the first manuscript entitled ‘Evolution of public health policy on healthcare self-management: the case of Ontario, Canada’, used archival research methods combining document review and evaluation to identify specific factors that have influenced the development of healthcare self-management policies over time in Ontario. Seventy-two documents on self-management of health were retrieved, analyzed, and evaluated using Walt and Gilson’s model for policy analysis. Findings suggested that self-management of health was introduced into policies in the early 2000s with a focus on diabetes and chronic conditions. Very few policies had a specific focus on older adults, and technology was introduced as a tool to support self-management in the context of healthcare delivery and enhancing healthcare infrastructure. Additionally, the factors that have influenced the evolution of policies over time include pressures on the healthcare system, hybrid top-down and bottom-up policymaking, and the political context. Phase 2, which is presented in the second manuscript entitled ‘Policymaker perspectives on self-management of disease and disabilities using information and communication technologies’ used a qualitative approach to identify the current environment for policymaking on the topic older adults’ self-management of disease and disability using ICTs. Ten policymakers from four different ministries in the Government of Ontario participated in semi-structured interviews. The analysis revealed that policies, in the form of programs, services, legislation and regulations, are the result of collaboration and dialogue between different actors and via a set of complex government processes. In addition, policy actions come from a plethora of sectors which all get influenced by predictable and unpredictable external pressures. The environment for policymaking was found to be mostly reactive to external pressures, while organized within a set of complex processes and collaborations. Phase 3, which is presented in the manuscript entitled ‘Validation of a framework for policymaking on self-management of health by older adults using technologies’ used a quantitative approach to validate a provisional framework for policymaking. Nine participants answered the survey questions, and some offered unsolicited insights. The results revealed that the provisional framework adequately captured the areas that should compose a framework for policymaking for older adults’ self-management of disease and disability using ICTs in Ontario. Participants noted the need to further explore and define certain concepts of the provisional framework, and that other relevant concepts should be added to the framework. The study proposes a refined framework which offers an opportunity for policymakers to advance the policy agenda for older adults’ self-management of disease and disability using ICTs. Policymakers working in the realm of older adults’ self-management of disease and disability are faced with a rapidly evolving and changing context where technologies are becoming omnipresent. With policies often lagging the consideration and inclusion of technology, a framework that supports a coordinated and holistic approaches to policymaking can enhance proactivity and cohesive actions from governments to consider their application. This can lead to better health outcomes for older adults living in this innovative and everchanging ecosystem.